2014
DOI: 10.4236/ajps.2014.521333
|View full text |Cite
|
Sign up to set email alerts
|

<i>Ustilaginoidea virens</i> Infection of Rice in Arkansas: Toxicity of False Smut Galls, Their Extracts and the Ustiloxin Fraction

Abstract: Cool, wet conditions in the southern US during the maturing stages of rice in 1998 contributed to outbreaks of false smut caused by Ustilaginoidea virens. Water extracts of false smut galls in Asia have been reported to contain ustiloxin toxins, cyclic peptide antibiotics that interfered with microtubule function and caused "lupinosis"-like lesions in mice. Cell-free extracts from false smut galls on rice grown in Arkansas were fractionated by a published procedure for the purification of ustiloxins. The ustil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 20 publications
0
21
0
Order By: Relevance
“…It is established that smut balls produce mycotoxins known as ustiloxins (Koiso et al, 1992). Ustiloxins are cyclic peptides, which are toxic to plants and animals by interfering with microtubule function, thereby inhibiting mitosis (Koiso et al, 1994;Abbas et al, 2014). Scientists, thus, raised concerns on direct impact of RFSm on seed germination and grain quality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is established that smut balls produce mycotoxins known as ustiloxins (Koiso et al, 1992). Ustiloxins are cyclic peptides, which are toxic to plants and animals by interfering with microtubule function, thereby inhibiting mitosis (Koiso et al, 1994;Abbas et al, 2014). Scientists, thus, raised concerns on direct impact of RFSm on seed germination and grain quality.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, published reports indicate impact of the disease on seed quality attributes such as reduction in individual grain weights (Singh et al, 1992;Hegde and Anahosur, 2000;Srivastava et al, 2014). Abbas et al (2014) showed that variation in germination of the disease contaminated seeds was specific to rice varieties. There has been no report on the effect of seed germination in the RFSm contaminated seeds in Bangladesh.…”
Section: Characteristicallymentioning
confidence: 99%
“…Ustiloxins could inhibit the mitosis of garlic root tip cells, but it did not inhibit cell elongation . Abbas et al (2014) demonstrated that the extract of U. virens from Arkansas, USA, had almost no effect on rice seed germination, but it did exhibit toxicity to duckweed.…”
Section: Toxicity To Plantsmentioning
confidence: 99%
“…Frequently, sclerotia can be observed on the surface of false smut balls. In addition to yield losses, U. virens produces ustiloxins that are toxic to human and animals and can inhibit radicle and plumule growth in plant seedlings (Abbas 2014; Meng et al 2015; Wang et al 2017).…”
Section: Introductionmentioning
confidence: 99%